Implementation of Rest API in Sports Facilities and Infrastructure Finding Application in Yogyakarta City - Tegar Riandi Sutrisno; Adam (Journal of Informatics and Communication Technology (JICT), 2023)
Yogyakarta is a city that has many sports facilities and types of sports. However, not all sports facilities are known by the people of Yogyakarta, especially for migrants from outside the city. So that a sports venue search mobile application is needed that can provide information about sports facilities, the need for sports facility information that can be accessed whenever and wherever the user is. Based on the above problems, it is proposed to create an android-based nearest sports venue search system. This system determines the location of the nearest facilities and infrastructure from the user's position by calculating the distance from two coordinate points and displayed on google maps and displaying the route to the nearest sports venue from the user. The result of this research is an android-based sports facilities and infrastructure location search application by utilizing GPS geolocation that can detect the coordinates of smartphone users and can display distances, road routes, and location updates. This application uses a data collection method by observation and identifying problems to test applications that are in accordance with community and functional needs. By utilizing Location-Based Services technology, it also increases the convenience of application users who want to exercise. After this sports venue search application is perfect, it will be able to run on the latest android or can run on ios for further features in the development of this application.